Joyful Learning in Elementary School - Soetam Rizky Wicaksono (International Journal of Theory and Application in Elementary and Secondary School Education, 2020)
Teaching in elementary school is another challenge for most teachers. While kids as students considered as hard in creating good learning process, some researchers try to propose joyful learning for students in elementary school. However, many barriers come in that effort for real enjoyable learning environment. This chapter tries to propose mobile learning as option to create joyful learning. Since that mobile learning can includes many types of joyful learning components and its familiriaty to students, it means that should be easier for teachers to implement that. This chapter also tries to explain how can teachers create mobile learning easily, thus teachers themselves can feel enjoy in learning process. So, whenever both teachers and students already feel their happiness, they will also express their enthusiasm as one of the most important thing in creating joyful learning